Determinan Transparansi dan Akuntabilitas Pengelolaan Keuangan Daerah dan Implikasinya Terhadap Kepercayaan Public-Stakeholders - Baiq Nurrizkiana; Lilik Handayani; Erna Widiastuty (Universitas Muhammadiyah Yogyakarta, Indonesia, 2017)
This research aimed to examine the influence of the financial statements presentation and accessibility toward transparency and accountability of regional financial management, followed by examine the influence of transparency and accountability of regional financial management toward the trust of Public-stakeholders. This research is explanatory research. Sampling in this research using purposive sampling method, then determined a sample of 233 respondents from internal public-stakeholders as many as 83 people, namely 30 heads and 30 chief financial officer of SKPD/agencies, and 23 auditors of East Lombok district government inspectorate, with consideration that they are understand and responsible for the presentation and availability of financial statements. Samples are derived from external public-stakeholders as many as 50 members of Parliament in East Lombok, 35 NGO activists / Management Foundation, 35 journalists who are users of financial information and 30 businessmen taxpayer / levy. Analysys methods used in testing the hypothesis is the Partial Least Square Analysis. The results showed that the financial statements presentation and accessibility partially positive and significant influence toward the transparency and accountability of regional financial management. Similarly with the transparency and accountability of regional financial management partially positive and significant influence toward the trust of public-stakeholders.